2020
DOI: 10.3390/en13184803
|View full text |Cite
|
Sign up to set email alerts
|

Shaping High Efficiency, High Temperature Cavity Tubular Solar Central Receivers

Abstract: High temperature solar receivers are developed in the context of the Gen3 solar thermal power plants, in order to power high efficiency heat-to-electricity cycles. Since particle technology collects and stores high temperature solar heat, CNRS (French National Center for Scientific Research) develops an original technology using fluidized particles as HTF (heat transfer fluid). The targeted particle temperature is around 750 °C, and the walls of the receiver tubes, reach high working temperatures, which impose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…A more central heliostat field or a more vertical (instead of tilted) tower cladding would lead to higher optical efficiency when applying the aiming point strategy. Upscaling this receiver technology with an adapted heliostat field layout leads to thermal efficiency above 80% [16]. In a commercial power plant, the objective would be to reach a particle temperature as high as possible (~750 • C), which could be achieved by increasing the tubes' height.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more central heliostat field or a more vertical (instead of tilted) tower cladding would lead to higher optical efficiency when applying the aiming point strategy. Upscaling this receiver technology with an adapted heliostat field layout leads to thermal efficiency above 80% [16]. In a commercial power plant, the objective would be to reach a particle temperature as high as possible (~750 • C), which could be achieved by increasing the tubes' height.…”
Section: Discussionmentioning
confidence: 99%
“…where x peak is the vertical location of the maximum flux density and b is a parameter that allows modification of the shape of the vertical distribution (flat or sharp). Although previous studies showed that the mean flux density on the receiver must not exceed 500 kW/m 2 to avoid hot spots [16], the limiting factor in this study is the maximal wall temperature given by the thermal model (presented below). Consequently, the maximum flux density can be slightly higher than 500 kW/m 2 in tube section where the temperature difference between the wall and the particles is at its maximum.…”
Section: Methodsmentioning
confidence: 98%
“…Above 30 kg/(m 2 s), it ranges between 60 and 75 %. The low values of 𝜂𝜂 at low particle mass fluxes are due to the high temperatures of the particles and the tubes that lead to high radiative losses [10]. Simultaneously, the particle temperature decreases with 𝐺𝐺 𝑝𝑝 , and reaches between 100 and 350 °C above 30 kg/(m²s) depending on the incident solar flux.…”
Section: Receiver Efficiencymentioning
confidence: 99%
“…In the particle-in-tube concept, the turbulent fluidization regime is reached with an aeration flow rate of around 1.7 sm 3 /h according to the previous results. At industrial scale, a 50 MW th solar receiver is feasible with 360 tubes based on preliminary calculations, and an overall electrical power of approximately 15 MW [6,7]. The geometry of the receiver and the dispenser were simulated, and an air flow rate of 2700 sm 3 /h was calculated to obtain the same fluidization velocity in the dispenser as in this paper.…”
Section: Synthesismentioning
confidence: 99%
“…Third, the same medium can be used as HTF and storage material. At large scale and high temperature (>700 • C), the use of a cavity is needed to improve thermal efficiency by reducing thermal losses [6]. Furthermore, high operation temperatures open the route for high-temperature thermodynamic cycles that improve the heat-to-electricity efficiency [7].…”
Section: Introductionmentioning
confidence: 99%